INNOVATION AS SENSUAL BASIS OF SOCIAL LIFE: PROBLEMS AND PERSPECTIVES - Мелков, Ю. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with philosophical analyses of the notion of innovation and innovative society. The attempt of creating of the project called to correct the civilization guiding lines of the XXI c. mankind on the bases of transformation of technogenic society into creative one is made.